2020
DOI: 10.1038/s41569-020-0422-8
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation tissue-engineered heart valves with repair, remodelling and regeneration capacity

Abstract: M. Y. (2021). Next-generation tissue-engineered heart valves with repair, remodelling and regeneration capacity. Nature Reviews Cardiology, 18(2), 92-116.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
136
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 244 publications
0
136
0
Order By: Relevance
“…Since then, a significant amount of research has been conducted to regenerate different tissues, as indicated by the number of publications on the regeneration each of skin, cartilage, bone, and heart-valves ( Figure 1 ). Skin and bone regeneration gained the most interest of researchers due to their simplicity compared to heart valves, which required specialized structures [ 35 ]. However, with the development in material science and fabrication techniques, particularly the use of 3D printing technologies to print biopolymer-based scaffolds, many specialized and highly accurate scaffolds have been successfully fabricated for the regeneration of most body tissues, including heart-valves [ 68 ].…”
Section: Tissue Scaffolding and Regenerative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Since then, a significant amount of research has been conducted to regenerate different tissues, as indicated by the number of publications on the regeneration each of skin, cartilage, bone, and heart-valves ( Figure 1 ). Skin and bone regeneration gained the most interest of researchers due to their simplicity compared to heart valves, which required specialized structures [ 35 ]. However, with the development in material science and fabrication techniques, particularly the use of 3D printing technologies to print biopolymer-based scaffolds, many specialized and highly accurate scaffolds have been successfully fabricated for the regeneration of most body tissues, including heart-valves [ 68 ].…”
Section: Tissue Scaffolding and Regenerative Medicinementioning
confidence: 99%
“…Biopolymer-based aerogels have been widely investigated and reviewed for their properties [ 24 ], fabrication techniques [ 25 ], biocompatibility [ 26 ], and cytotoxicity [ 27 , 28 ]; many studies have revealed their potential in tissue engineering as well as other biomedical applications [ 25 , 29 , 30 , 31 ]. Previous reviews either explain a single type of tissue regeneration such as skin [ 32 ], bone [ 33 ], cartilage [ 34 ], or valves [ 35 ], and many of these reviews focus on a particular scaffold-based material such as chitosan [ 36 ] or cellulose [ 37 ]. Furthermore, biopolymer hydrogel-based scaffolds have been extensively reviewed in many previous reviews, including [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further work in this field has sought to define an ideal PVR, with the goal of creating an “off-the-shelf” TEPV capable of self-renewal and growth within pediatric patients. While the concept of tissue engineering encompasses advantages over current technology [ 38 ], this section will focus solely on select studies regarding synthetic, bioabsorbable TEPV scaffolds.…”
Section: Tissue-engineered Pulmonary Valvementioning
confidence: 99%
“…Conventional approaches to deliver growing heart valve replacement are based on tissue engineering or mechanical engineering but these approaches have failed in clinical translation (5)(6)(7)(8)(9). This is a critical barrier to progress in the field.…”
Section: Introductionmentioning
confidence: 99%